Compromising the plasma membrane as a secondary target in photodynamic therapy-induced necrosis. Issue 18 (1st October 2018) - Thompson, Sebastian A.; Aggarwal, Amit; Singh, Sunaina; Adam, Alejandro P.; Tome, Joao P.C.; Drain, Charles Michael
Graphical abstract: Abstract: Photodynamic therapy (PDT) is a non-invasive treatment widely applied to different cancers. The goal of PDT is the photo-induced destruction of cancer cells by the activation of different cell death mechanisms, including apoptosis and/or necrosis. Recent efforts focusing on understanding the mechanisms of cell death activated by PDT find that it depends on the type of photosensitizer (PS), targeted organelles, and nature of the light used. It is generally accepted that very short incubation times are required to direct the PS to the plasma membrane (PM), while longer periods result in the accumulation of the PS in internal compartments such as the endoplasmic reticulum or mitochondria. Glycosylation of the PS targets cancer via saccharide receptors on the cell surface, and is generally assumed that these compounds rapidly internalize and accumulate, e.g. in the endoplasmic reticulum. Herein we demonstrate that a minor fraction of a glycosylated chlorin compound residing at the PM of cancer cells can activate necrosis upon illumination by compromising the PM independently of the length of the incubation period . The results presented here show that the PM can also be targeted by glycosylated PS designed to accumulate in internal organelles. PS activation to induce necrosis by compromising the plasma membrane has the benefits of fast cell death and shorter irradiation times. The findings described here expand our understanding of the cellular damage induced by phototherapies, presenting the possibility of activating another cell death mechanism based on the incubation time and type of light used.